Factors Contributing to the Level of Fear in Public Speaking Among Third-Year College Teachers Education Students: An Assessment: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study was conducted to determine the factors that contribute to the level of fear of publicspeaking among third-year College of Teachers Education (CTE) students. The researchersbelieve that it's high time for learners in higher education to understand how important it is tonot only be able to speak in front of an unforgiving audience but to ace it every time there's acall for them to do so. This is a challenge that will hone their public speaking skills as theyforay into the real world of professionals.Based on the result, the majority of the factors that contribute to the level of fear in publicspeaking come out to be the audience relationship. The study also revealed that most of thestudents facing public speaking experienced factors of audience relations, where respondentsfelt fear when faced with an unfamiliar crowd when presenting publicly. This studyrecommends that respondents become more prepared the day before the presentations toprevent situations that will make them feel anxious and have stage fright.The study urged the researchers to be driven to produce solution-based recommendations,for instance, tips and guidelines that would help high school learners not only reduce buteradicate speech anxiety. The researchers have come up with a public speaking guide thatwill help college students not only know and understand how to be able to speak before thepublic but also make sure that they get their message across in the most effective and truthfulway possible.
Keywords: Psychology